Sejarah dan Fungsi Masjid Syekh Zainal Abidin di Pudun Julu, Kecamatan Batunadua, Kota Padangsidimpuan - Rambe, Ahmad Zubeir; Ritonga, Sakti; Nasution, Kasron (Local History & Heritage, 2024)
This research examines the history and development of Syekh Zainal Abidin Mosque in Pudun Julu, Batunadua District, Padangsidimpuan, using a historical methodology approach. Built in 1880 AD, the mosque serves as an exemplar of Islamic architectural art, reflecting the evolution of Islam and the process of Islamization in Padangsidimpuan. The mosque is named after its founder, Syekh Zainal Abidin, also known as Harahap (1811-1901). Initially serving as a center for spiritual activities, political affairs during the colonial era, an educational institution, a place for traditional spiritual practices (parsulukan), and a medical center. However, presently, its function is primarily focused on being a place of worship, without involving religious and social rituals as in the past. This transformation reflects the mosque's adaptation to changing times while preserving its spiritual values. This study provides insights into the dynamic roles of the mosque within the local context.